BREAST LUMPS AND HISTOPATHOLOGICAL FINDINGS IN A TERTIARY HEALTH FACILITY IN NORTH –CENTRAL NIGERIA: A FIVE YEAR REVIEW - J, Bulus; S, Gidado; I, Pate; F, Golwa; J, Shuai’bu; K, Bangs; B, Dawam (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Breast lumps are common reasons why majority of females irrespective of age present to the surgical out-patient departments (SOPD). Breast lumps are either benign or malignant. A greater percentage of breast lumps that present are benign but breast lumps evokes anxiety and it is important to allay the fears of presenting with breast lumps. Aim: To determine the frequency of breast lumps and their histopathological findings Materials and Methods: The study was a five year retrospective review from January,2012 to January,2017 of female patients who presented with breast lump, had excision/biopsy and histology reports of biopsy samples. Ethical clearance was obtained from the institutional review board. The demographic details, symptom on presentation and histopathology result were documented and analyzed using epiinfo 16 versions.